Recent Advances in Strategies for the Cloning of Natural Product Biosynthetic Gene Clusters - Wang, Wenfang; Zheng, Guosong; Lu, Yinhua (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial natural products (NPs) are a major source of pharmacological agents. Most NPs are synthesized from specific biosynthetic gene clusters (BGCs). With the rapid increase of sequenced microbial genomes, large numbers of NP BGCs have been discovered, regarded as a treasure trove of novel bioactive compounds. However, many NP BGCs are silent in native hosts under laboratory conditions. In order to explore their therapeutic potential, a main route is to activate these silent NP BGCs in heterologous hosts. To this end, the first step is to accurately and efficiently capture these BGCs. In the past decades, a large number of effective technologies for cloning NP BGCs have been established, which has greatly promoted drug discovery research. Herein, we describe recent advances in strategies for BGC cloning, with a focus on the preparation of high-molecular-weight DNA fragment, selection and optimization of vectors used for carrying large-size DNA, and methods for assembling targeted DNA fragment and appropriate vector. The future direction into novel, universal, and high-efficiency methods for cloning NP BGCs is also prospected.